The Safety of Electroconvulsive Therapy in Patients With Implanted Deep Brain Stimulators: A Review of the Literature and Case Report. Issue 2 (June 2019) - Peroski, Michael S.; Chu, Michael M.; Doddi, Seshagiri Rao; Regenold, William T.
Abstract : Abstract: Currently there is no consensus statement about the safety of electroconvulsive therapy in patients who have implanted electrodes for deep brain stimulation. We present a summary of the existing literature on this topic, consisting of 21 cases, and then report a case performed at the University of Maryland Medical Center. Notably, with appropriate safety precautions and careful patient selection, there were no adverse events reported in the literature that were related to the presence of the deep brain stimulation device in any of the cases. Based on our review of the literature and the case we present, we have found no evidence so far to indicate that electroconvulsive therapy in patients with an implanted deep brain stimulator is unsafe.